A presença haitiana no Brasil : o município de Mandaguari, PR como um estudo de caso - Rosseto, Daniele (2018)
The population?s mobility is a historical feature of the reality of Haiti. This was due to the political, economic, and social consequences of the Black Revolution in the nineteenth century, the greatest effect of which has been the intensification of migratory flows. Initially, the routes of this mobility were directed to the countries of Central America and the Caribbean itself and also to countries in North America, such as the United States, a major destination. This trend has changed in recent years as Haitian mobility has turned to countries such as Brazil, due to its growing international visibility as an emerging country and also by the barriers imposed by the US government's migration policies. In the southern region, Haitian migratory flow, driven by industrial growth and the great demand for labor, led to the concentration of a considerable number of immigrants living in the region. The main activities carried out by the Haitians in the labor market were related to the production lines in the industries, especially those related to the activity in poultry abattoirs and slaughterhouses. Between 2010 and 2013 the northern region of Paraná welcomed an increasing number of these immigrants, especially in Maringá and Mandaguari cities, which partly justified the choice and territorial delimitation of our research. Regarding the issue of labor, Mandaguari city, in need of labor attracted these immigrants, however, there were some difficulties, such as the insertion of women in the labor market. Support networks were created through the Catholic Church to help families in need. Many advances have become noticeable, such as the creation of an association - the Association of Foreigners of Mandaguari (ASSEM) - that allowed a greater socialization of the group. It can be noted that the constitution of the support networks provided conditions for the arrival of new Haitian immigrants, building in the Brazilian reality the identity of this flow. Therefore, the daily life of these immigrants was analyzed with the purpose of knowing the conditions and strategies used by them to adapt themselves to this new space